2015
DOI: 10.1089/jop.2014.0140
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Pharmacokinetics Comparison Between 0.2% Olopatadine and 0.77% Olopatadine Hydrochloride Ophthalmic Solutions Administered to Male New Zealand White Rabbits

Abstract: The newly developed 0.77% olopatadine hydrochloride ophthalmic solution formulation resulted in a higher and more prolonged olopatadine concentration in the target tissue, that is, conjunctiva compared to the commercial formulation of 0.2% olopatadine ophthalmic solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
2
17
0
Order By: Relevance
“…Superior efficacy of olopatadine 0.77% over 0.1% and 0.2% formulations was recently shown in Phase III clinical trials 14,15. In a pre-clinical study, olopatadine 0.77% formulation showed improved solubility and a 4-fold increase in the concentration of olopatadine in the aqueous humor when compared to olopatadine 0.2%, with no sign of capacity-limit kinetics 16. Likewise, in the conjunctiva, a slightly greater dose proportional increase in olopatadine was observed after an ocular dose of olopatadine 0.77% compared with olopatadine 0.2%, suggesting potentially longer anti-allergic activity.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Superior efficacy of olopatadine 0.77% over 0.1% and 0.2% formulations was recently shown in Phase III clinical trials 14,15. In a pre-clinical study, olopatadine 0.77% formulation showed improved solubility and a 4-fold increase in the concentration of olopatadine in the aqueous humor when compared to olopatadine 0.2%, with no sign of capacity-limit kinetics 16. Likewise, in the conjunctiva, a slightly greater dose proportional increase in olopatadine was observed after an ocular dose of olopatadine 0.77% compared with olopatadine 0.2%, suggesting potentially longer anti-allergic activity.…”
Section: Discussionmentioning
confidence: 91%
“…In a preclinical study, olopatadine was observed at higher concentrations with prolonged presence in the target tissue (rabbit conjunctiva) following dosing with olopatadine 0.77% compared to that with olopatadine 0.2% 16. The new olopatadine 0.77% formulation has demonstrated a longer, 24-hour duration of action and superior efficacy compared to olopatadine 0.2% formulation in Phase III clinical studies 14,15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two phase 3 studies were conducted using the CAC model to assess the safety and efficacy of olopatadine HCl 0.77% in patients with allergic conjunctivitis 1215. The outcomes of these two studies supported the recent approval (January 30, 2015) of olopatadine HCl ophthalmic solution 0.77% (olopatadine HCl 0.77%) by the FDA for the treatment of ocular itching associated with allergic conjunctivitis.…”
Section: Introductionmentioning
confidence: 86%
“…This new formulation contains olopatadine HCl at a concentration of 0.77% (7.76 mg/mL), which is equivalent to 0.7% olopatadine as a free base 12. Olopatadine HCl 0.77% was developed with the rationale of expanding the benefits offered by olopatadine 0.2%, particularly superior and long-lasting relief over a period of 24 hours with once-daily dosing, while maintaining its safety and patient comfort.…”
Section: Introductionmentioning
confidence: 99%